Analisa Hukum Putusan Nomor 22/G/2021/PT.Tun Jkt Dalam Kasus Pemberhentian Dengan Hormat ASN Dengan Disabilitas Mental Menurut Hukum Administrasi Negara - Ikhsan, Rafly Noer; HZ, Evi Deliana; Zulhidayat, Muhammad (Jurnal Ilmiah Wahana Pendidikan, 2025)
State Civil Service Employees (or abbreviated as ASN Employees) are Civil Servants and Government Employees with a Work Agreement who are appointed by Government Officials or entrusted with other State duties and are paid based on statutory regulations. People with disabilities basically have the same opportunities as other normal people, especially in serving the country, one of which is becoming a Civil Servant, because every citizen has an equal opportunity to become an ASN by going through several requirements. As stated in Article 56 of Law Number 5 of 2014 on State Civil Apparatus, the requirements referred to in this article are candidates for Civil Servants who are appointed as Civil Servants, and for this there are several requirements such as having to graduate first in Education. , must be physically and mentally healthy, but physical and spiritual health will be adjusted for people with disabilities, then this will be adjusted to work needs. In this article, the requirements for becoming a Civil Servant and for implementing and maximizing the performance of workers with disabilities who will work as Civil Servants in the relevant agency are outlined. This research will examine the main problem according to the scope and identification of the problem through a normative juridical approach. Based on normative research methods, the data source used in this research is a secondary data source consisting of 3 legal materials, namely: primary legal materials, secondary legal materials, and tertiary legal materials. Data collected from literature study. Legal Analysis of Decision Number 22/G/2021/PT.TUN JKT in the Case of Respectfully Dismissing ASN with Mental Disabilities According to State Administrative Law because this decision is an important precedent for the protection and fulfillment of the rights of mental disabilities in Indonesia because it requires consideration of legal certainty and legal protection.